INVENTORY DATA PROCESSING WAREHOUSE RECEIPTS IN DEPO MAKMUR APPLICATIONS USING VISUAL BASIC 6.0 - Aldi Marwoto; Ire Puspa Wardhani, SKom., MMSI Ire Puspa Wardhani, SKom., MMSI (Jurnal Sistem Informasi, 2005)
Scientific writing is about the use of applications in the processing of a database onDepo Makmur. Visual Basic is a program where the application designer andMicrosoft Access Database as its data storage.This application was specially made for the use of Depo Makmur in which the authorobtained the data for use in this writing. Where the authors hope this application canbe useful and can be used with the best. This application can shorten the time formaking reports and simplify the processing of data.